2018
DOI: 10.1242/dev.156521
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin facilitates zygotic genome activation in zebrafish

Abstract: At zygotic genome activation (ZGA), changes in chromatin structure are associated with new transcription immediately following the maternal-to-zygotic transition (MZT). The nuclear architectural proteins cohesin and CCCTC-binding factor (CTCF) contribute to chromatin structure and gene regulation. We show here that normal cohesin function is important for ZGA in zebrafish. Depletion of the cohesin subunit Rad21 delays ZGA without affecting cell cycle progression. In contrast, CTCF depletion has little effect o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 89 publications
1
37
0
Order By: Relevance
“…We compared our data with recently published ATAC-seq based chromatin accessibility data . Weak ATAC-seq signals which did not meet the standard cutoffs in Liu et al 2018 andMeier et al 2018 were detectable when aligned on all TFBS (Fig. 1D).…”
Section: Nanog Individually or In Combinationmentioning
confidence: 99%
“…We compared our data with recently published ATAC-seq based chromatin accessibility data . Weak ATAC-seq signals which did not meet the standard cutoffs in Liu et al 2018 andMeier et al 2018 were detectable when aligned on all TFBS (Fig. 1D).…”
Section: Nanog Individually or In Combinationmentioning
confidence: 99%
“…A key stage in development is the transition from the maternal to zygotic control of transcription (also termed zygotic genome activation; ZGA). Embryos with reduced levels of cohesin (RAD21) retain elevated levels of maternal mRNAs, suggesting that cohesin is critical for maternal mRNA turnover and subsequent expression of zygotic mRNAs (Rosa and Brivanlou, 2017;Meier et al, 2018). In embryos that contain wild-type levels of cohesin, ChIP-seq revealed an extensive increase in the number of cohesin-decorated DNA sites post-ZGAespecially at enhancers and/or promoters that carry histone modifications indicative of activated genes (Bogdanovic et al, 2012;Meier et al, 2018).…”
Section: Cohesins Promote Tads But Antagonize Compartmentsmentioning
confidence: 99%
“…Embryos with reduced levels of cohesin (RAD21) retain elevated levels of maternal mRNAs, suggesting that cohesin is critical for maternal mRNA turnover and subsequent expression of zygotic mRNAs (Rosa and Brivanlou, 2017;Meier et al, 2018). In embryos that contain wild-type levels of cohesin, ChIP-seq revealed an extensive increase in the number of cohesin-decorated DNA sites post-ZGAespecially at enhancers and/or promoters that carry histone modifications indicative of activated genes (Bogdanovic et al, 2012;Meier et al, 2018). If cohesins regulate transcription on a gene-by-gene basis, one would expect that those genes identified through altered mRNA levels would be the same genes that exhibit cohesin-binding to their enhancers and/or promoters.…”
Section: Cohesins Promote Tads But Antagonize Compartmentsmentioning
confidence: 99%
“…The nature of the relationship between zygotic transcription and chromatin regulation has been uncertain. Chromatin regulation could precede and initiate zygotic transcription (Meier et al, 2018;Østrup et al, 2013). Conversely, zygotic transcription may help shape chromatin structure, a model that has been tested by several studies: A study that analyzed the spatial genome organization in fly embryos revealed that early expressed genes correlate with the boundaries of Topologically Associating Domains (TADs).…”
Section: Zygotic Transcription and Chromatin Organizationmentioning
confidence: 99%